Replication termination for staphylococcal plasmids: plasmids pT181 and pC221 cross-react in the termination process. - Iordanescu, S (1988)
We present data which indicate that (i) the origin of replication of plasmids pT181 and pC221 can also function as termination signals; (ii) termination of replication occurs when a round of replication initiated either by RepC at the pT181 origin or by RepD at the pC221 origin reaches either of these origins, proving that the two plasmids cross-react for termination of replication; and (iii) the replication initiated at the origin of another staphylococcal plasmid, pE194, does not terminate at the origin of pT181 or pC221, indicating the existence of a specific relationship between the initiation and termination of a replication event.